Dieta hiperlipídica provoca alterações fenotípicas e funcionais no útero das gerações parental e F1 prenhes - Salles, Évila Da Silva Lopes (2019)
It is known that obesity and the consumption of a high fat diet are related to reproductive failure and to the fetal programming event and that the immune cells present in the pregnant uterus may be involved in these events. Among the uterine immune cells, the activity of the uterine Innate Lymphoid Cells (uILC) is highlighted, especially the uNK DBA+ cells. These cells are like sentinels of the maternal-fetal interface, since they are able to recognize and respond to the most varied alterations of the maternal organism, besides having an important role in the processes of decidualization, implantation and formation of the placenta. The hypothesis of this study is that the consumption of high-fat diet (HF) during gestation can affect the uterine environment, the uNK cells biologyand promoted event of fetal programming, resulting in the alteration of uNK cells of F1 generation pregnant. Ninety females of Swiss mice mated with males of the same lineage. On the morning when the vaginal plug was detected the females were divided into 2 groups which consumed the diets from the 1st day of gestation (gd) up to the moment of euthanasia: MCD (mothers fed with control diet) and MHF (mothers fed with high-fat diet). 45 MCD and 45 MHF females were euthanized at 6th, 10th and 14th gd. It was analyzed the weight gain, adipose tissue area, gestational viability, uNK cells morphology and stereology, perforin and caspase-3 cleaved immunofluorescence, gene expression of perforin, granzyme B, Ly49A, Ly49B, interferon gamma (IFNγ), vascular endothelial growth factor α (VEGFα), tumor necrosis factor α (TNFα), Toll Like receptor 4 (TLR4), Interleukin-1β (IL-1β) Growth factor (TGF-β1), Interleukin-17a (IL-17a) and Cytokine 3 signaling suppressor (SOCS 3) in the basal decidua and analysis of uILC by flow cytometry. It was also used 12 MCD and 12 MHF animals that were fed with the diets during the whole gestation to obtain the control (F1CD) and HF (F1HL) offspring. On the 2nd postnatal day (PND) the offspring were standardized in 8 to 10 pups, the number of females always equal the number of males, and the fostering procedure was also performed. The weight gain and naso-anal length of the offspring were analyzed. After the 60th PND the females were mated with non-parental males and were euthanized at 10th gd. Pregnant females were evaluated for gestational weight gain, gestational viability, uNK cells morphology and stereology, immunofluorescence for perforin and 3-cleaved caspase, and analysis of perforin expression in the maternal decidua. The results showed that the MHF group had significant weight gain and increase of the adipose tissue area, in the decidua of these females were found a large number of uNK DBAlow cells and non-reactive perforin cells in the 3 regions of SI at 10th and 14th gd and increase in the number of 3-cleaved caspase positive cells. The gene expression showed an increase of perforin and granzyme mRNA levels and low expression of Ly49A, IFN-γ, IL-1β and IL- 17α at the 6th gd. At 14th gd there was a decrease in the expression of VEGFα, TNFα, TGF-β1 and SOCS3. In the F1HF group there was a reduction in postnatal growth and an increase in the Lee index in the 60th PND. Significant increase in weight and mean area of adipose tissue and the Lee index at 10th gd were also observed. On the same day a large number of DBAlow uNK cells, a decrease in perforin positive cells and an increase in the incidence of 3-cleaved caspase positive cells in the decidua were observed as well as a significant reduction in perforin expression. Thus, it can be concluded that consumption of a high-fat diet during pregnancy triggers not only changes in the maternal uterine environment, but also promotes the fetal programming event, generating in the offspring changes very similar to those observed in the mothers who consumed the diet.